EKSPRESI CYTOSOLIC ASPARTATE-SPECIFIC CYSTEINE PROTEASE-3 (CASPASE-3) PADA JARINGAN HATI RATTUS NORVEGICUS (WISTAR) SETELAH PEMBERIAN SUBKRONIK AFLATOKSIN B1 (AFB1) - Maritha, Indah Dina; Supranowo, Supranowo; Lyrawati, Diana (Fakultas Kedokteran Universitas Brawijaya, 2006)
Aflatoksin B1(AFB1) is one of the toxic agents produced by Aspergillus flavus that frequently contaminates foods not properly stored. AFB1 undergoes biotransformation which may result in the production of reactive oxygenspecies (ROS) hazardous to liver cells. Following a cascade of oxidative reaction, ROS will cause the mitochondria torelease cytochrome c which subsequently activates caspase-3, leading to apoptosis. In this present study we evaluated the effect of aflatoxin B1 on the expression of caspase-3 in the liver. AFB1 was administered per oral, at different dosage and length of exposure, subchronically. This study was carried out as a factorial designed experiment with two factors. The first was dosage factor i.e 0, 10, 15 and 20 µg (0; 0,05; 0,075; 0,1 µg/g BW) and the second was exposure time factor i.e. 12, 16 and 20 weeks. Rattus norvegicus strain Wistar aged approximately eight weeks old and weighed 180-200 g were used as the experimental animals. The expression of caspase-3 was examined by using immunohistochemistry. The results showed that the expression of caspase-3 increased significantly (p = 0,000) with the escalation of AFB1 in dosage and/or exposure time (p = 0,001). In the interaction between dose and exposure time of AFB1an increase in the expression of caspase-3 was also observed (p = 0,000). Interestingly, these studies also revealed thatin the liver tissues there was a limitation in the expression of caspase-3, where the raising of further AFB1 dosage and length of exposure were not followed by further increase of the caspase-3.